Taxpayer Interest in Paying Vehicle Tax Compliance - Gede Surya Wibawa; Gayatri (E-Jurnal Akuntansi, 2024)
This research aims to obtain empirical data regarding taxpayer interest in fulfilling motor vehicle tax in the midst of the Covid-19 pandemic. Hypothesis testing is used to determine the effect of exogenous variables on endogenous variables through the use of SEM-PLS on 100 respondents determined through the purposive sampling method. The data analysis technique uses Structural Equation Modeling–Partial Least Square (SEM-PLS) with the SmartPLS3 application. The results of this research are the relaxation program for Motor Vehicle Tax and Motor Vehicle Title Fee, SAMSAT Corner, Taxpayer awareness has a positive influence on Taxpayer compliance, but the location variable has no effect on Taxpayer compliance.